Elaboration of an alcoholic drink by using byproducts of the coffee benefit process (coffee pulp) - Cortés Rico, Martha Elizabeth
The development of a fermented alcoholic beverage was sought, using the pulp of the coffee to achieve a product with pleasant sensorial characteristics that when consumed, evidences the origin. Coffee pulp is used as raw material, taking into account the high environmental impact that this byproduct generates in coffee ecosystems. It is known that during the process of benefit of coffee are obtained a large number of byproducts that are not used, exceeding 60% of the grain weight and in a high percentage correspond to the pulp.The development of the product was based on the characterization of the raw material, both physicochemical and microbiological, three beverage prototypes were developed using various pulpmucilage blends. The results of the prototypes were evaluated taking into account the sensory profile and the production process. The best behavior prototype was chosen and finally the standardization of the production process was made. It was possible to obtain as a final result, a drink that sensorially conserves characteristics to coffee and according to its productive process, is easy to implement and produce.